Pengungkapan Emisi Karbon dan Pengungkapan ESG terhadap Efisiensi Investasi dengan Fleksibilitas Keuangan sebagai Variabel Moderasi - Nuryadin, Sausan Syahirah; Astuti, Christina Dwi (VISA: Journal of Vision and Ideas, 2024)
This research refers to the current issue related to investment efficiency carried out by major energy and infrastructure companies, which can certainly be influenced by various factors even though sustainable accounting is applied by the company. With this problem, the author raises several variables to obtain knowledge related to the relationship of the influence given by the Carbon Emission Disclosure and ESG Disclosure variables on Investment Efficiency with the Financial Flexibility moderation variable. The analysis method used in this study is a panel data model with purposive sampling technique. In this study, the data used uses secondary data taken from annual reports and sustainability reports on major energy and infrastructure sector companies listed on the Indonesia Stock Exchange from 2020 to 2022. From the results of the research that has been conducted, it can be concluded that the Carbon Emission Disclosure variable has a positive influence on Investment Efficiency, another positive influence is given by ESG Disclosure on Investment Efficiency, and Financial Flexibility moderates or strengthens the influence of Carbon Emission Disclosure on Investment Efficiency, but Financial Flexibility cannot strengthen the influence of ESG Disclosure on Investment Efficiency.